The Effect of Work Motivation and Organizational Commitment on Job Satisfaction at the Population and Civil Registration Office of Barito Kuala Regency - Wurnongo, Wulan; Ahmad Alim Bachri (HM Publisher, 2022)
An organization needs to increase its attention to the quality of its employees, both in terms of the quality of knowledge and skills, career, and level of welfare, so as to improve employee performance to achieve organizational goals. This study aims to determine the effect of work motivation and organizational commitment on job satisfaction for employees of the population and the civil registration office of Barito Kuala Regency. This research is an explanatory causality study with a quantitative approach. The research location is the Department of Population and Civil Registration, Barito Kuala Regency, South Kalimantan, Indonesia. The subjects of this study were all staff who worked at the Department of Population and Civil Registration of Barito Kuala Regency, totaling 70 people. Measurement of variables using a Likert scale technique with a weight scale from 1 to 5. To determine the effect of the variables studied, multiple linear regression analysis was used. The results of the analysis show that work motivation has a negative and significant effect on job satisfaction. The higher the work motivation of an employee, the lower the level of job satisfaction, and organizational commitment has a positive and significant effect on job satisfaction. In conclusion, the higher the organizational commitment that exists in an employee, the higher the level of job satisfaction of employees at the Department of Population and Civil Registration of Barito Kuala Regency.